Enhancing electroreduction of CO2 over Bi2WO6 nanosheets by oxygen vacancies. Issue 10 (29th April 2019) - Chu, Mengen; Chen, Chunjun; Guo, Weiwei; Lu, Lu; Wu, Yahui; Wu, Haihong; He, Mingyuan; Han, Buxing
Abstract : The rich oxygen vacancies in Bi2 WO6 nanosheets can efficiently enhance CO2 electroreduction to CO. Abstract : Bi2 WO6 nanosheets with plentiful oxygen vacancies were synthesised, and were highly efficient for the electroredution of CO2 to CO. The faradaic efficiency of CO could reach 91% with a high current density of 43 mA cm −2 at low potentials. The oxygen vacancies could enhance the reaction effectively by improving the adsorption and activation of CO2 .